Synthesis, characterization and evaluation of stearyl acrylate-co-behenyl acrylate copolymer as a pour point depressant of waxy crude oil - Ridzuan, Norida; Kamal, Yusoh; Norhayati, Abdullah; Basem, Elarbe; Ibrahim, Elganidi; Shamala Vijaya, Kumar (Springer Science and Business Media Deutschland GmbH, 2022)
Pour point depressant (PPD) has the competitive advantage of lowering the temperature of the wax appearance (WAT) and crude oil viscosity. In this paper, a novel PPD of poly stearyl acrylate-co-behenyl acrylate (SA-co-BA) in various mass ratios (1:1, 2:1, 3:1, 1:2 and 1:3) was effectively synthesized by solution radical polymerization method, and characterized by fourier transform infrared FTIR, proton nuclear magnetic resonance NMR, x-ray diffraction XRD and scanning electron microscopy SEM. The SA-co-BA PPD was evaluated on Malaysian crude oil via the pour point, the rheological and cold finger analysis to prevent the wax deposition at low temperature and improve flowability. The findings showed that the mass ratio (1:1) at 1000 ppm has a positive effect on the pour point depression from 11 to 2 °C. It was investigated from the rheological measurement that the viscosity of crude oil increases as the temperature decreases. Whereas, the viscosity decreases as the shear rate increases and as shear rate increases, shear stress increases. The flowability performance of the crude by the mass ratio of 1:1 at 1000 of the SA-co-BA concentrations have improved by 89.76%. The highest paraffin inhibition efficiency PIE of wax deposited was obtained at 1:1 of the mass ratio by 44.14%, indicating the smallest amount of wax is formed. This finding is interestingly attributed to the acrylate groups that have a long alkyl chain. Thus, SA-co-BA copolymer was demonstrated to be an appreciable pour point depressant that can prevent the wax deposition at low temperature and increasing the flowability of Malaysian crude oil.